Malaysian tourism demand from the Middle East Market: a preliminary analysis - Norlida Hanim,; Redzuan Osman,; Abu Hassan Ashari Mohd Noor,; Mohd Safar Hasim, (Institut Kajian Rantau Asia Barat, 2010)
The 11th September 2001 tragedy had greatly altered the global tourism scenario. The free flow of tourists to tourist destinations was to some extent had been restricted due to the safety and security reasons. In additions some major tourist destinations have imposed more restrictions and stringent regulations to the inbound tourists for the same reasons. Tourists especially from the Muslim countries were becoming more careful and selective in choosing their holiday destinations. Statistic has shown that the arrival of Middle East tourists to the United States had declined sharply after the incidence. For example in 2000 about 249,260 Middle East tourists visited the USA but in 2002 and 2005 the numbers had decreased sharply to 126,613 and 144,131 respectively. Similarly their arrivals to the UK, during the same period the numbers declined from 429,000 to 360,000 and 380,000. Tourists from this region started to find alternative destinations for their holidays. Malaysia as an Islamic country is one of their choices. Their arrivals to Malaysia have shown an increasing trend. For example in 1998 about 19,571 arrivals were recorded. By 2002 and 2005 the numbers had increased to 126,239 and 145,861. This paper is trying to investigate statistically did the 11th September incidence is a significant factor influencing the increasing of Middle East tourist arrivals to Malaysia besides other factors such as tourist expenses in Malaysia, tourist income, traveling expenses at alternative tourism destinations and dummy for September 11,2001 tragedy. In estimating the importance of these factors, panel analysis method will be utilized. Empirical results have shown that the Random Effects method/model is the best. Overall results are acceptable. They are consistent with tourism demand theory and satisfying the statistical requirement.